Are Older Adults Less Embodied? A Review of Age Effects through the Lens of Embodied Cognition - Costello, Matthew C.; Bloesch, Emily K. (Frontiers in Psychology, 2017)
Embodied cognition is a theoretical framework which posits that cognitive function is intimately intertwined with the body and physical actions. Although the field of psychology is increasingly accepting embodied cognition as a viable theory, it has rarely been employed in the gerontological literature. However, embodied cognition would appear to have explanatory power for aging research given that older adults typically manifest concurrent physical and mental changes, and that research has indicated a correlative relationship between such changes. The current paper reviews age-related changes in sensory processing, mental representation, and the action-perception relationship, exploring how each can be understood through the lens of embodied cognition. Across all three domains, older adults exhibit a characteristic tendency to favor visual processing over bodily factors, leading to the conclusion that older adults are less embodied than young adults. We explore the significance of this finding in light of existing theoretical models of aging and argue that embodied cognition can benefit gerontological research by identifying further factors that can explain the cause of age-related declines.